Development strategy to improve accreditation at the Faculty of Administrative University of Jakarta - Dasli, Aira Putri Eri (Priviet Social Sciences Journal, 2025)
This study aims to analyze study program development strategies to improve accreditation at the Faculty of Administrative, University of Jakarta. This research used a qualitative descriptive approach, including interviews, observations, and documentation with various relevant parties such as deans, heads of study programs, lecturers, administrative staff, and students. The study concluded that the study program development strategy to improve accreditation includes, first, strengthening the study program's vision and mission. Second, planning and implementing quality assurance in accordance with standards is required. Third, monitoring and evaluating quality control to ensure measurability is required. This strategy can ensure the quality of national education through a sustainable, internal quality assurance system. In the implementation of Tridharma, teaching, research, and community service activities have been actively carried out. Lecturers routinely conduct research and community service and encourage student involvement through theses and social activities. However, instances of manual documentation practices still exist, which slow down the evidence collection process during accreditation. Therefore, accelerating digitalization, both by optimizing SIAKAD and developing a cloud-based storage system, has become a key priority for the university.